Effects of Extraction Process Factors on the Composition and Antioxidant Activity of Blackthorn (Prunus spinosa L.) Fruit Extracts - Ana-Maria Dr; Aurelian Cristian Boscornea; Ana-Maria Brezoiu; Ștefan Theodor Tomas; Oana Cristina Pârvulescu; Raluca Stan (MDPI AG, 2023)
This study aimed at establishing the optimal conditions for the classic extraction of phenolic compounds from Prunus spinosa L. fruits. The effects of different parameters, i.e., ethanol concentration in the extraction solvent (mixture of ethanol and water), operation temperature, and extraction time, on process responses were evaluated. Total phenolic content (TPC), total anthocyanin content (TAC), antioxidant capacity (AC), and contents of protocatechuic acid (PA), caffeic acid (CA), vanillic acid (VA), rutin hydrate (RH), and quercetin (Q) of fruit extracts were selected as process responses. A synergistic effect of obtaining high values of TPC, TAC, AC, PA, and VA was achieved for the extraction in 50% ethanol at 60 °C for 30 min. At a higher level of process temperature, the extraction of protocatechuic acid and vanillic acid was enhanced, but the flavonoids, i.e., rutin hydrate and quercetin, were degraded. A lower temperature should be used to obtain a higher amount of flavonoids. TPC, TAC, AC, and phenolic acid contents (PA, CA, and VA) in the extract samples obtained at an ethanol concentration of 50-100%, a temperature of 30-60 °C, and an extraction time of 30 min were strongly directly correlated.